Higher Education and Sustainability : Opportunities and Challenges for Achieving Sustainable Development Goals. - Azeiteiro, Ulisses; Davim, J. Paulo (Higher Education and Sustainability series., 2019)
The book provides descriptions of experiences from research and educational sustainability projects and the role HEIs can play together with contributions presenting a variety of initiatives showing how SDGs are being implemented. The book promotes the theoretical and practical understanding on this thematic and disseminates knowledge and international research and cooperation. Contributions cover the role of SDGs in advancing implementation of sustainable development, sustainability in higher education, the role of universities in sustainable development, new paths towards sustainable development and e-learning contributions. Features Focuses on theoretical and practical understanding on Sustainability, Higher Education and SDGs to disseminate knowledge and promote research and cooperation Includes lessons learned from sustainability research and educational challenges presenting case studies, technological developments, outputs of research and studies, best practices and examples of successful projects Discusses relevant and international perspectives on sustainability, higher education and SGDs Presents local and international contributions on a variety of initiatives showing how SDGs are being implemented